Storytelling: One Package Learning in Improving Language Skill and Implanting Character Education on Children - Niswatin Nurul Hidayati (Tarbiyah Departement collaboration with AMCA, 2019)
The development of technology makes the world become narrow and various kinds of information and shows become easy to access, including by children. Various kinds of acts of violence, crime, even videos or content that are not yet suitable for children to watch are more easily accessible through devices. This has a negative impact on the lives of the nation's children, for example theft, sexual violence, and brawl committed by children and adolescents. Thus, the inculcation of moral values ​​by both parents and teachers becomes a